Respon Alumni Program Studi IPA UNM Terhadap Workshop Pembuatan Alat Peraga IPA Sebelum Dan Sesudah Workshop - Rifda Nur Hikmahwati Arif; Salma Samputri; Nurfitra Yanto; Rifda Mardian Arif; Sitti Saenab (Sakura Digital Nusantara, 2023)
Adjusting to developments in learning, educators are required to be creative and the quality of human resources must be improved through educational channels using science teaching aids. The research results obtained were that the response from alumni of the program study Science Education UNM before the workshop on making science props was 100% very interested in taking part in the workshop on making props and the response from alumni of program study Science Education UNM after the workshop on making science props was 76.5% of participants after it was held There will be a continuation of the workshop on making science teaching aids to develop teaching aids in science learning in Biology, Physics and Chemistry. Therefore, training or workshops on making science teaching aids were held for alumni of the program study Science Education UNM.